’We Here Highly Resolve’: The End of Compromise and the Return of Revolutionary Time - Forbes, Robert Pierce (Conceived in Liberty: Perspectives on Lincoln at Gettysburg, 2015)
Keywords: dept.his

"Grating the Nutmeg: Slavery, Race and Sectionalism in Connecticut from the Colonial Era to the Civil War" - Forbes, Robert Pierce (Connecticut History, 2013)
Keywords: dept.his; ⛔ No DOI found

“The Cause of This Blackness”: The Early American Republic and the Construction of Race - Forbes, Robert Pierce (American Nineteenth Century History, 2012)
Race is routinely defined as “socially constructed,” from which it follows that there was a time before its construction. What that time looked like, and how Africans were then viewed by white Americans, is difficult to perceive from a vantage point within the paradigm of race. This essay considers important but neglected cultural referents to argue that a binary distinction between black and white did not emerge on theoretical grounds until the 1780s, when Jefferson's Notes on the State of Virginia shrewdly redirected growing challenges to slavery into quasi-metaphysical reflections on the gulf between whites and blacks.
1 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/14664658.2012.681949
Keywords: Thomas Jefferson; dept.his; race